Pattern of Retained Contrast on Immediate Postprocedure Computed tomography (CT) After Particle Embolization of Liver Tumors Predicts Subsequent Treatment Response - Wang, Xiaodong (Cardiovasc Intervent Radiol, 2012)
PURPOSE: To determine if the pattern of retained contrast on immediate postprocedure computed tomography (CT) after particle embolization of hepatic tumors predicts modified Response Evaluation Criteria in Solid Tumors (mRECIST) response. MATERIALS AND METHODS: This study was approved by the Institutional Review Board with a waiver of authorization. One hundred four liver tumors were embolized with spherical embolic agents (Embospheres, Bead Block, LC Bead) and polyvinyl alcohol. Noncontrast CT was performed immediately after embolization to assess contrast retention in the targeted tumors, and treatment response was assessed by mRECIST criteria on follow-up CT (average time 9.0 ± 7.7 weeks after embolization). Tumor contrast retention (TCR) was determined based on change in Hounsfield units (HUs) of the index tumors between the preprocedure and immediate postprocedure scans; vascular contrast retention (VCR) was rated; and defects in contrast retention (DCR) were also documented. The morphology of residual enhancing tumor on follow-up CT was described as partial, circumferential, or total. Association between TCR variables and tumor response were assessed using multivariate logistic regression. RESULTS: Of 104 hepatic tumors, 51 (49 %) tumors had complete response (CR) by mRECIST criteria; 23 (22.1 %) had partial response (PR); 21 (20.2 %) had stable disease (SD); and 9 (8.7 %) had progressive disease (PD). By multivariate analysis, TCR, VCR, and tumor size are independent predictors of CR (p = 0.02, 0.05, and 0.005 respectively). In 75 tumors, DCR was found to be an independent predictor of failure to achieve complete response (p <0.0001) by imaging criteria. CONCLUSION: TCR, VCR, and DCR on immediate post-treatment CT are independent predictors of CR by mRECIST criteria.